Evaluating interactive R-Shiny based mathematics learning media through motivation and engagement pathways in border-region schools - Simarmata, Justin Eduardo; Purnomo, Miko; Fallo, Kristoforus (Journal on Mathematics Education, 2026)
Persistent disparities in mathematics learning outcomes between urban and border-area schools underscore enduring structural inequities linked to limited access to effective, contextually appropriate digital learning environments. Although technological integration in education has expanded substantially, empirical research examining the pedagogical effectiveness of interactive computational platforms—such as those developed using R-Shiny—remains limited, particularly in geographically marginalized regions. This study investigates the effectiveness of R-Shiny-based interactive mathematics learning media in enhancing students’ conceptual understanding and learning achievement. A quantitative research design employing a pretest–posttest approach was utilized, supported by validated questionnaires administered to 101 tenth-grade students enrolled in senior high schools along the Indonesia-Timor Leste border. Data were analyzed using Confirmatory Factor Analysis (CFA) to establish construct validity and Structural Equation Modeling (SEM) to test hypothesized relationships among learning motivation, student engagement, user satisfaction, conceptual understanding, and perceived academic performance. Descriptive statistics revealed consistent improvements in posttest scores relative to pretest results, signifying measurable gains in conceptual understanding. Moreover, SEM analysis indicated that learning motivation, student engagement, and user satisfaction each exerted positive and statistically significant effects on conceptual understanding, which in turn significantly predicted perceived academic performance. Collectively, these findings suggest that R-Shiny-based interactive media foster not only improved cognitive outcomes but also strengthen motivational and engagement-related processes that mediate mathematics learning in geographically disadvantaged educational settings.